Effects of navigated TMS on object and action naming - Hernandez-Pavon, Julio C.; Mäkelä, Niko; Lehtinen, Henri; Lioumis, Pantelis; Mäkelä, Jyrki P. (Frontiers in Human Neuroscience, 2014)
Transcranial magnetic stimulation (TMS) has been used to induce speech disturbances and to affect speech performance during different naming tasks. Lately, repetitive navigated TMS (nTMS) has been used for non-invasive mapping of cortical speech-related areas. Different naming tasks may give different information that can be useful for presurgical evaluation. We studied the sensitivity of object and action naming tasks to nTMS and compared the distributions of cortical sites where nTMS produced naming errors. Eight healthy subjects named pictures of objects and actions during repetitive nTMS delivered to semi-random left-hemispheric sites. Subject-validated image stacks were obtained in the baseline naming of all pictures before nTMS. Thereafter, nTMS pulse trains were delivered while the subjects were naming the images of objects or actions. The sessions were video-recorded for offline analysis. Naming during nTMS was compared with the baseline performance. The nTMS-induced naming errors were categorized by error type and location. nTMS produced no-response errors, phonological paraphasias, and semantic paraphasias. In seven out of eight subjects, nTMS produced more errors during object than action naming. Both intrasubject and intersubject analysis showed that object naming was significantly more sensitive to nTMS. When the number of errors was compared according to a given area, nTMS to postcentral gyrus induced more errors during object than action naming. Object naming is apparently more easily disrupted by TMS than action naming. Different stimulus types can be useful for locating different aspects of speech functions. This provides new possibilities in both basic and clinical research of cortical speech representations.